Pancasila Legal Theory and Indonesia's Marine Economic Rights Management in International Law - Sitorus, Andi Putra; Suhaidi, Suhaidi (Media Syari'ah, 2023)
As long as the government is unable to properly manage natural resources, the maritime economic rights of Indonesia will continue to be poorly managed, resulting in a significant loss of the country's marine wealth to other countries. Protecting Indonesia's marine resources requires an applicable legal theory. Pancasila's legal theory can provide answers since the principles it upholds have always been at the heart of Indonesian society. This justice and civilization need the state to correctly use its rights and obligations and not take away the maritime resources of other countries; therefore, these principles should be adopted by the entire country. By assembling information on Indonesia's marine riches and legal theory resources such as the Pancasila legal theory, this study aims to establish norms in the field.Selama pemerintah tidak mampu mengelola sumber daya alam dengan baik, hak ekonomi maritim Indonesia akan terus tidak terkelola dengan baik, sehingga kekayaan laut negara hilang secara signifikan ke negara lain. Melindungi sumber daya laut Indonesia membutuhkan teori hukum yang aplikatif. Dalam hal ini, teori hukum Pancasila dapat memberikan jawaban karena prinsip-prinsip yang dijunjungnya selalu ada di dalam jiwa masyarakat Indonesia. Keadilan dan peradaban ini membutuhkan negara untuk menggunakan hak dan kewajibannya dengan benar dan tidak merampas sumber daya maritim negara lain. Oleh karena itu, prinsip-prinsip ini harus diadopsi oleh seluruh negara. Dengan menghimpun informasi kekayaan laut Indonesia dan sumber teori hukum seperti teori hukum Pancasila, kajian ini bertujuan untuk menetapkan norma-norma pada tataran praktis.